2015
DOI: 10.1096/fj.15-271783
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid desaturase 2 (FADS2) gene product catalyzes Δ4 desaturation to yield n-3 docosahexaenoic acid and n-6 docosapentaenoic acid in human cells

Abstract: Docosahexaenoic acid (DHA) is a Δ4-desaturated C22 fatty acid and the limiting highly unsaturated fatty acid (HUFA) in neural tissue. The biosynthesis of Δ4-desaturated docosanoid fatty acids 22:6n-3 and 22:5n-6 are believed to proceed via a circuitous biochemical pathway requiring repeated use of a fatty acid desaturase 2 (FADS2) protein to perform Δ6 desaturation on C24 fatty acids in the endoplasmic reticulum followed by 1 round of β-oxidation in the peroxisomes. We demonstrate here that the FADS2 gene prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 61 publications
6
117
0
Order By: Relevance
“…The final steps were long thought to be by direct Δ4-desaturation via 22:5n-3→22:6n-3. Biochemical data in rat liver developed in the 1990s established an alternative coupled microsomal-peroxisomal pathway via 22:5n-3→24:5n-3→24:6n-3→22:6n-3, where the last step is one round of β-oxidation in the peroxisomes [3]. Molecular studies since 2001 established that Δ4-desaturase (FADS2) is the final step in marine microorganisms (e.g.…”
Section: Lcpufa Biosynthesismentioning
confidence: 99%
See 3 more Smart Citations
“…The final steps were long thought to be by direct Δ4-desaturation via 22:5n-3→22:6n-3. Biochemical data in rat liver developed in the 1990s established an alternative coupled microsomal-peroxisomal pathway via 22:5n-3→24:5n-3→24:6n-3→22:6n-3, where the last step is one round of β-oxidation in the peroxisomes [3]. Molecular studies since 2001 established that Δ4-desaturase (FADS2) is the final step in marine microorganisms (e.g.…”
Section: Lcpufa Biosynthesismentioning
confidence: 99%
“…Molecular studies since 2001 established that Δ4-desaturase (FADS2) is the final step in marine microorganisms (e.g. Thraustochytrium), marine teleost fish, and mammals, and very recently in humans [3]. …”
Section: Lcpufa Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Park et al (54) reported that Fads2 transcript in human cells can catalyze 4-desaturation and be actively involved in direct synthesis of DHA from 22:5n-3. While we did not detect any effects on the DHA level in Elovl2 / pups fed by Elovl2 / mothers, the maternal genotype appeared to have a significant impact on the expression levels of the desaturases, but not on Elovl5.…”
Section: Discussionmentioning
confidence: 99%